Proposed Marketing Communication for KAI Access Application Based On Consumer Product Knowledge (The Indonesian Journal of Business Administration, 2021)
A mobile application is one of the major approaches that many service companies obtained to provide convenient service for the customers. PT. KAI (Kereta Api Indonesia) tried to make their services more accesible by releasing a mobile app called KAI Access. However, it was initially found that only 40% of KAI customers use the mobile application. This study aimed to identify the current knowledge of KAI customers about KAI Access mobile app using AIDA model (Attention/awareness, Interest, Desire, and Action) and to find out the gap between product knowledge and consumer attention. This study used quantitative research and was conducted by collecting primary data by using a questionnaire. 400 respondents were selected as research sample representing the staggering 2.409.000 active customers of KAI services. The result of gap ranking demonstrated the priority sequence on the mobile app user interface, supporting factors for customers to use the apps. This finding suggests that PT. KAI must develop the application to be visually attractive, easier to use continuously updated, and most importantly, to be more recognizable and interesting for KAI customers by providing adequate socialization and promotion by coordinating all the IT, marketing, and product distribution department.Keywords: KAI Access, marketing, mobile application, product knowledge.